Effects of particle size distribution on the explosion severity of coal dust. Issue 17 (2nd September 2021) - Zhang, Jiangshi; Sun, Longhao; Nie, Fangchao; Zhou, Hejun
ABSTRACT: The effects of particle size distribution (PSD) on coal dust explosion severity were investigated using a 20 L vessel. The severity was evaluated by the maximum explosion pressure ( P e x ), the maximum rate of pressure rise ( ( d P / d t ) e x ), and the time spans ( t 1, t 2 ) between ignition and P e x and between ignition and ( d P / d t ) e x during a trial. These parameters of five coal samples with the same particle size span (PSS) and different PSD were measured at 250 g / m 3 . The results show that the explosion rate is greatly affected by PSD. When the finer particles account for 30 wt%, ( d P / d t ) e x increased significantly, whereas t 1 and t 2 values decreased. ( d P / d t ) e x, t 1 and t 2 are affected significantly by D 10 and D 50 (the particle size for which 10% and 50% of the particles by projection area) dust components. It is suggested that D 10 and D 50 should be considered when polydispersity is used to describe the PSD. D 10, D 50, and the Specific Surface Area(SSA) are related to these explosion parameters and provide the better description of the PSD. The smaller the particle size is, the more complete the particles combust and the smaller the calorific values of dust explosion products are.